Odpowiedzi

Najlepsza Odpowiedź!
2010-04-06T12:11:01+02:00
D) x+1/2+x=x+2/3 /*6
6x+3+6x=6x+4
6x=4-3
6x=1
x=¹/₆

e) 3x+2/4+5=2x+1/3 /*6
18x+3+30=12x+2
18x-12x=2-3-30
6x=-31
x= - ³¹/₆= -5 ¹/₆

f) 4-x/5=8-x/4 /*20
80-4x=160-5x
-4x+5x=160-80
x=80

g) 5+2x/0,5=8+6x/5
5+4x=8+6x/5 /*5
25+20x=40+6x
14x=15
x=1¹/₁₄

h) 4-x+2/7=8x-3+2x/-10 /*70
280-70x+20=560x-210-14x
-70x-560x+14x=-210-280-20
-616x=-510
x=510/616=255/308

i) 2(x+1)-3/4=x/5 /*20
40(x+1)-15=4x
40x+40-15=4x
40x-4x=-40+15
36x=-25
x= - 25/36

7/216
a) x(x-4)+56=x²
x²-4x+56=x²
-4x=-56
x=14

b) 2x(5+x)-2=6(x-2)+2x²
10x+2x²-2=6x-12+2x²
10x-6x=-12+2
4x=-10
x=- 10/4= -2½

c) (x-1)(x+2)=(x+3)(x+4)
x²+2x-x-2=x²+4x+3x+12
2x-x-4x-3x=12+2
-6x=14
x= -14/6=-2⅓
2010-04-06T12:24:44+02:00
D) x+1/2+x=x+2/3
x+x-x=⅔-½
x=1/6
e) 3x+2/4+5=2x+1/3
3x-2x=⅓-2/4-5
x=-1/6-5
x=-5/1/6
f) 4-x/5=8-x/4 *20
80-4x=160-5x
-4x+5x=160-80
x=80
g) 5+2x/0,5=8+6x/5 *10
50+40x=80+12x
40x-12x=80-50
28x=30 /28
x=30/28
h) 4-x+2/7=8x-3+2x/-10


a) x(x-4)+56=x²
x²-4x+56=x²
-4x=-56 /-4
x=1.25
b) 2x(5+x)-2=6(x-2)+2x²
10x+2x²-2=6x-12+2x²
10x-6x=-12+2
4x=10 /4
x=10/4
x=2.5
c) (x-1)(x+2)=(x+3)(x+4)
x²+2x-x-2=x²+4x+3x+12
2x-x-4x-3x=12+2
-6x=14 /-6
x=-14/6